Risk and Finance in the Coffee Sector : A Compendium of Case Studies Related to Improving Risk Management and Access to Finance in the Coffee Sector - World Bank (World Bank, Washington, DC, 2015)
Millions of coffee farmers and coffee trading enterprises lack sufficient credit. This is partly due to myriad challenges and considerable costs that formal lending institutions face serving rural, often isolated markets. A better understanding of coffee sector risks is needed to respond with strategies, training, and tools that can help farmers and enterprises, mitigate their exposure to risk, and strengthen their resilience against inevitable shocks. This report explores the role that producer associations, governments, non-profit organizations, the private sector, and other intermediaries can play in making risk management and financing tools more accessible and more workable for smallholder coffee growers. It examines the global coffee sector and outlines: (1) major risks and constraints facing the sector; (2) potential opportunities for improving the management of certain risks; and (3) programs launched in various regions aimed at improving access to finance. Through the use of detailed case studies taken from a number of coffee-producing countries, this report seeks to demonstrate: how risks can arise that adversely impact on the coffee sector and those working within the sector; how risks can be better managed so that the sector is able to improve its resilience; how financing constraints can be overcome through a variety of innovative approaches; and how there are potential opportunities to both improve risk and access to finance in a coordinated manner. This report highlights the need for collaboration among all stakeholders within the coffee sector, both nationally and globally. The final two cases demonstrate a virtuous circle of improved risk management that generates improved access to finance, which itself facilitates further improvements in risk management. To this end, this report considers the global coffee supply chain and the actors operating within it, and demonstrates, through the use of selected case studies, how collaborative efforts by actors and stakeholders can improve risk management and access to finance. It shows how risks can be mitigated and or transferred between supply chain actors, and how coping can be facilitated through cooperative arrangements for when risks arise.